2019
DOI: 10.1186/s43042-019-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis and abortion: pro- and anti-inflammatory cytokines gene expression of the host immune cells

Abstract: Background: Toxoplasmosis during pregnancy is known for inducing variable serious outcomes. In many previous studies, pregnancy was evaluated as a single event while in reality; it has different distinct immunological stages depending on gestational time and possible external factors as infectious agents. A state of immunological balance as well as a state of maternal-fetal tolerance should be established; otherwise, atypical unwelcomed outcomes might occur as a result of such infection Aim: This work aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Only one study was published in the predatory journal name ( 43 ). The eligible articles were conducted in China ( 39 ), Iran ( 38 ), Colombia, in collaboration with the United States ( 40 ), India ( 43 ), Egypt ( 41 ), Mexico ( 42 , 44 ) and Brazil ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study was published in the predatory journal name ( 43 ). The eligible articles were conducted in China ( 39 ), Iran ( 38 ), Colombia, in collaboration with the United States ( 40 ), India ( 43 ), Egypt ( 41 ), Mexico ( 42 , 44 ) and Brazil ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that the level of placental TGF-β level was decreased in mice including adverse pregnancy outcomes after Toxoplasmosis infection [9]. Other study reported that TGF-β levels were raised in pregnant with acute T. gondii contagion in contrast to those of uninfected pregnant [21].…”
Section: Discussionmentioning
confidence: 97%
“…T. gondii Infection can result in adverse pregnancy consequences [9]. Some researchers showed that the immune system secreted cytokines and lymphocytes maintain maternal tolerance to the stability of paternal alloantigen's during normal pregnancy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasmosis cause degrees in Tregs and lead to pregnancy miscarriage [4]. Interferon-γ (IFN-γ) is a specific parasitic cytokine that prevents replication and improves its conversion from tachyzoite to bradyzoite stage but its inhibit trophoblast growth result in fetal death and abortion [5].…”
Section: Introductionmentioning
confidence: 99%